2015
DOI: 10.5301/ejo.5000665
|View full text |Cite
|
Sign up to set email alerts
|

Study of Spectral-Domain Optical Coherence Tomography in Children: Normal Values and Influence of Age, Sex, and Refractive Status

Abstract: This study provides reference values for macular thickness, macular volume, and RNFL in healthy children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 31 publications
4
22
0
2
Order By: Relevance
“…In all studies reporting normative paediatric SD-OCT data of macular thickness, the thinnest area of the macula was the central area. [1][2][3][4][5][6]8 Our result was consistent with this finding. Additionally, we found that the inner circle subfield was significantly thicker than the outer circle subfield, which also was congruent with most of the previous studies.…”
Section: Macular Thicknesssupporting
confidence: 83%
See 4 more Smart Citations
“…In all studies reporting normative paediatric SD-OCT data of macular thickness, the thinnest area of the macula was the central area. [1][2][3][4][5][6]8 Our result was consistent with this finding. Additionally, we found that the inner circle subfield was significantly thicker than the outer circle subfield, which also was congruent with most of the previous studies.…”
Section: Macular Thicknesssupporting
confidence: 83%
“…[2][3][4][5][6] However correlation with gender has been found by some authors. For example, in Rao's study, average RNFL thickness was significantly higher in females.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations